PELATIHAN PEMBUATAN DAN PEMASARAN BATIK ECOPRINT SERTA MAPPING DUSUN JELAPAN PUNDONG BANTUL DAERAH ISTIMEWA YOGYAKARTA - Gunawan, Barbara; Anugrah, Rinasa Agistya (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The purpose of the KKN PPM Community Service program is to help increase the economic value of the community from the sale of Batik eco print. From mapping outcomes, it expects that newcomers will know the layout of the Jelapan, and to improve the quality of education and education in the community, especially children from the KKN teaching program. The problem with Mitra is that residents are not familiar with eco print batik, do not yet have a picture of its packaging and marketing mechanisms. Residents of Jelapan also have not received education about mapping the hamlet, which is very useful.Â The solutions offered to solve these problems are 1) the socialization of natural resource utilization programs held in the Jelapan; the outcome of this socialization activity is the understanding and awareness of residents about the use of natural resources into artistic-valued and selling products, so that citizens, especially mothers and young women in the Jelapan can fill time with useful activities that increase income; 2) organized training and assistance in making eco print batik, the outputs of this activity are residents, especially women and young women able to make batik using eco print techniques, 3) training and marketing assistance provided for eco print batik, the outcome is citizens can market and sell batik products eco print, 4) hamlet mapping formed, the result of this activity was a hamlet mapping that would be useful for various activities; 5) learning assistance held for PAUD, TK, and TPA children. It consists of 10 students from different study programs; for 1.5 months, there are activities.